2014
DOI: 10.1002/mnfr.201300764
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion improved the anti‐inflammatory effect of amaranth (Amaranthus hypochondriacus) hydrolysates in LPS‐induced human THP‐1 macrophage‐like and mouse RAW 264.7 macrophages by preventing activation of NF‐κB signaling

Abstract: Amaranth hydrolysates inhibited LPS-induced inflammation in human and mouse macrophages by preventing activation of NF-κB signaling. Extrusion improved anti-inflammatory effect of amaranth hydrolysates in both cells, which might be attributed to the production of bioactive peptides during processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 44 publications
9
58
0
3
Order By: Relevance
“…Also, the increase in ROS produce the activation of NF-κB, likewise some other markers such as IL-1α, SDF-α and IL-32/α/β/γ also activate NF-κB [27,43]. NF-κB is a family of transcription factors involved in many pathways including inflammation [26]. In our previous work [26] we found peptides from amaranth hydrolysates with potential antioxidant capacity and anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the increase in ROS produce the activation of NF-κB, likewise some other markers such as IL-1α, SDF-α and IL-32/α/β/γ also activate NF-κB [27,43]. NF-κB is a family of transcription factors involved in many pathways including inflammation [26]. In our previous work [26] we found peptides from amaranth hydrolysates with potential antioxidant capacity and anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Extrusion, a high temperature–short time technology, has been used to obtain pre-cooked flours with high nutritional value [24], antioxidant capacity and anti-inflammatory activity [25,26]. Montoya-Rodríguez et al [26] reported, in extruded amaranth flour, peptides with active sequences and potential antithrombotic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated NF-κB is involved in immune regulation, inflammatory response, cell growth, and antiapoptosis via phosphorylating IκB and shifting into the nucleus [40][41][42]. Notably, previous studies have shown that the suppression of NF-κB pathway is associated with anti-inflammatory responses [43][44][45][46]. Therefore, we explored whether GEA could regulate NF-κB signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…within the beans like the trypsin inhibitors and lipoxygenases (Atienzo Lazos et al, 2011). Extrusion enhanced the anti-inflammatory effect of amaranth (Amaranthus hyochondriacus) flour soluble protein hydrolysates (Montoya-Rodrí guez et al, 2014a;Montoya-Rodrí guez et al, 2014b;Montoya-Rodrí guez et al, 2015). Extrusion and germination have already been successfully used to improve common beans nutritional properties and the development of new food products (Kelkar et al, 2012;López et al, 2013;Nyombaire et al, 2011;Simons et al, 2014;Vidal-Valverde et al, 2002).…”
Section: Introductionmentioning
confidence: 99%